Hedging - wybrane zagadnienia - Szeląg, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The term hedging is based on the verb "to hedge", which means "to give protection against something" or "to surround". In business, this term is used to denote methods of reducing or neutralizing risk of changes in prices of financial instruments or commodities by means of derivative instruments. To this end, the so-called hedge transactions are used. This term is understood as a position one takes in the futures market matched by one's position taken in the spot market. As a result potential losses on one transaction will be more or less balanced by profits on the other. The article examines the theoretical output on hedging. Furthermore, pros and cons of hedging transactions were presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 370-377